Effect Of Anemia On Cognitive Capacity Of Adult Students In Sokoto, Nigeria - Ai Umar; Yusuf Sarkingobir; Malami Dikko; Yusuf Yahaya Miya; Nura Maiakwai Salah (Jurnal Ilmiah Kesehatan, 2023)
Anemia due to iron deficiency or inherited sickle cells nowadays threatens public health in many respects. Among the effects of anemia is its ability to affect cognitive or related abilities. Thus, this study aimed to assess the effect of iron deficiency anemia and sickle cell anemia on the cognitive ability of participants in Sokoto. The study design involved recruiting 50 participants (25 healthy and 25 tested to be anemic) who were subjected to Montreal Cognitive Assessment. Another fifteen sickle anemia patients, and twenty-five healthy persons were evaluated using Montreal cognitive assessment. The scores of all the respondents were recorded and subjected to the X2 test and revealed significant differences at (p<0.05). The result of the study indicated that the anemic participants scored fewer mean marks (420.0 ± 14.0) in contrast to the healthy participants (820.0 ± 32.6) at (P<0.05). The effect of sickle cell anemia was revealed with a significant difference (p<0.05), showing that the healthy adult participants of the study scored higher marks (240.0 ± 16.0) compared to the anemic participants (924.0 ± 30.8). Thus, the anemia of any kind can potentially affect the cognitive capacity of students in the state.